Antidiabetic of Mango (Mangifera longipes Griff.) Leves: Methanol Extract, Water Fraction, and Ethyl Acetate - Nur Rahayuningsih; Piranti Piranti; Diana S. Zustika (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Mango leaves (Mangifera longipes Griff.) are used for diabetic, malaria, gastrointestinal, kidney, as well as topical treatment of wounds. The aim of this study was to determine the antidiabetic activity of methanol extract, water fraction and ethyl acetate fraction from mango leaves (Mangifera longipes Griff.). Oral Glucose Tolerance Test (OGTT) on 24 rats divided into 6 groups, namely normal; negative; positive (given acarbose 1.8 mg/200 g BW rats); methanol extract (EM), water fraction (FA), ethyl acetate fraction (FEA) with a dose of 58.8 mg/200 g BW rats. Induction of 1.35 g/200 g BW of rats glucose was carried out 30 minutes before the dosage administration. Data analysis with Paired T Test (95% confidence level). Results: In crude extract standardization, the water content was 2%, the ash content was 12.6% and the water soluble extract content was 19.5%. In crude extract and EM, flavonoids, saponins, and phenols were identified; in FA identified saponins and phenols; FEA identified flavonoids and phenols. A significant decrease in blood glucose levels at T0 and T120 in all groups (significant 2-tailed <0.05). The percentage of decline in the positive and FEA groups compared to the negative was 85.5% and 16.9%, respectively. Discussion:. Flavonoids are thought to increase antioxidant activity and inhibit α-glucosidase enzymes. Conclusion: EM, FA and FEA have antidiabetic activity with the best percentage reduction in glucose levels was FEA (16.9%).Keywords: Antidiabetic, OGTT, Mangifera longipes Griff